C. perfringens enterotoxin-claudin pore complex: Models for structure, mechanism of pore assembly and cation permeability - Santhosh Kumar Nagarajan; Joy Weber; Daniel Roderer; Jörg Piontek (Computational and Structural Biotechnology Journal)
The pore-forming Clostridium perfringens enterotoxin (CPE), a common cause of foodborne diseases, facilitates Ca2+ influx in enterocytes, leading to cell damage. Upon binding to certain claudins (e.g., claudin-4), CPE forms oligomeric pores in the cell membrane. While the mechanism of CPE-claudin interaction is well understood, the structure and assembly of the pore complex remain elusive. Here, we used AlphaFold2 complex prediction, structure alignment, and molecular dynamics simulations to generate models of prepore and pore states of the CPE/claudin-4 complex. We sequentially addressed CPE-claudin, CPE-CPE, and claudin-claudin interactions, along with CPE conformational changes. The CPE pore is a hexameric variant of the typical heptameric pore stem and cap architecture of aerolysin-like β-barrel pore-forming toxins (β-PFT). The pore is lined with three hexa-glutamate rings, which differ from other β-PFTs and confer CPE-specific cation selectivity. Additionally, the pore center is indicated to be anchored by a dodecameric claudin ring formed by a cis-interaction variant of an interface found in claudin-based tight junction strands. Mutation of an interface residue inhibited CPE-mediated cell damage in vitro. We propose that this claudin ring constitutes an anchor for a twisting mechanism that drives extension and membrane insertion of the CPE β-hairpins. Our pore model agrees with previous key experimental data and provides insights into the structural mechanisms of CPE-mediated cytotoxic cation influx.